2006
DOI: 10.1083/jcb.200508121
|View full text |Cite
|
Sign up to set email alerts
|

The Fat1 cadherin integrates vascular smooth muscle cell growth and migration signals

Abstract: The significance of cadherin superfamily proteins in vascular smooth muscle cell (VSMC) biology is undefined. Here we describe recent studies of the Fat1 protocadherin. Fat1 expression in VSMCs increases significantly after arterial injury or growth factor stimulation. Fat1 knockdown decreases VSMC migration in vitro, but surprisingly, enhances cyclin D1 expression and proliferation. Despite limited similarity to classical cadherins, the Fat1 intracellular domain (Fat1IC) interacts with β-catenin, inhibiting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(136 citation statements)
references
References 46 publications
4
131
1
Order By: Relevance
“…46 Although this translocation is no longer associated with poor prognosis in pediatric patients due to new and intensified chemotherapy, 47,48 they do suffer from increased risk of central nervous system relapse. 49,50 Previous reports have established high Fat1 expression within the central nervous system and its importance for central nervous system development, 14,51,52 and we therefore speculate that high Fat1 expression associated with the t(1;19)(E2A-PBX1) translocation, together with the ability of the cytoplasmic tail of Fat1 to directly bind b-catenin, 53 may provide another potential mechanism whereby ectopic Fat1 expression can either aid central nervous system infiltration or stabilize leukemia --stroma interactions with its unknown extracellular ligand. Finally, our laboratory has recently shown that the Fat1 protein is expressed as both an unprocessed full-length protein and furin-processed heterodimer on the surface of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…46 Although this translocation is no longer associated with poor prognosis in pediatric patients due to new and intensified chemotherapy, 47,48 they do suffer from increased risk of central nervous system relapse. 49,50 Previous reports have established high Fat1 expression within the central nervous system and its importance for central nervous system development, 14,51,52 and we therefore speculate that high Fat1 expression associated with the t(1;19)(E2A-PBX1) translocation, together with the ability of the cytoplasmic tail of Fat1 to directly bind b-catenin, 53 may provide another potential mechanism whereby ectopic Fat1 expression can either aid central nervous system infiltration or stabilize leukemia --stroma interactions with its unknown extracellular ligand. Finally, our laboratory has recently shown that the Fat1 protein is expressed as both an unprocessed full-length protein and furin-processed heterodimer on the surface of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FAT1 indirectly regulates cell proliferation; Hou et al demonstrated that the inhibition of FAT1 expression promotes cell proliferation whereas the overexpression of FAT1 suppresses proliferation in vascular muscle cells (10). Therefore, the inhibition of FAT1 expression was expected to increase the cell proliferation in the OSCCs as well.…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic domain of FAT1 binds to β-catenin and plays a pivotal role in cell migration, polarization and morphogenesis (3,(10)(11)(12)(13)(14)(15)(16). Therefore, the deletion of this gene could implicate the characteristics and biological behavior of OSCCs that involve cell adhesion, migration and/or invasion, which might result in poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, in the same experiment, we also tested the effect of growth factor stimulation by increasing the concentration of serum because the expression of FAT1 can be stimulated by serum in vascular smooth muscle cells (16). Fig.…”
Section: Fat1 Is Proteolytically Processed Before Achieving Cell Surfmentioning
confidence: 99%